Early experience with universal preprocedural testing for SARS-CoV-2 in a relatively low-prevalence area. (3rd March 2021) - Lewis, Sarah S.; Smith, Becky A.; Akinboyo, Ibukunoluwa C.; Seidelman, Jessica; Wolfe, Cameron; Kirk, Allan B.; Martin, Gavin; Denny, Thomas; Lobaugh, Bruce; Rehder, Catherine; Cardona, Diana; Lee, Mark J.; et al.
Abstract: We implemented universal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing of patients undergoing surgical procedures as a means to conserve personal protective equipment (PPE). The rate of asymptomatic coronavirus disease 2019 (COVID-19) was <0.5%, which suggests that early local public health interventions were successful. Although our protocol was resource intensive, it prevented exposures to healthcare team members.